KEDUDUKAN NOTARIS SEBAGAI MEDIATOR BERSERTIFIKAT DI DALAM DAN DI LUAR PENGADILAN - YESSIKALIASNA BR SEMBIRING (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Notaris Dr. Tony, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum The conclusion is that the position of a certified Notary as a mediator in and outside the Court does not violate Law No. 30/2004 on Notarial Position, Law No. 2/2014 on the Amendment of Law No. 30/2004 on Notarial Position, the Notarial Code of Ethics/2015, the Supreme Court’s Ruling No. 1/2016 on the Procedure of Mediation in Court, and the Guidance for Mediator’s Behavior No. 108/KMA/SK/VI/2016 since they do not firmly prohibit two positions for a Notary as a mediator. Even though the profession for a Notary as a mediator is under the official institutions, the Supreme Court and the Court; his fee does not come from these institutions but from the conflicting parties that appoint him as a mediator. It is recommended that a Notary be given legal certainty and legal protection in order to maintain him as a certified mediator in and outside the Court and at the same time as legal umbrella and a rule of thumb for him as a certified mediator in and outside the Court.Keywords: Position, Notary, Certified Mediator